Pest categorisation of Palm lethal yellowing phytoplasmas. (31st October 2017) - ,; Jeger, Michael; Bragard, Claude; Candresse, Thierry; Chatzivassiliou, Elisavet; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Gregoire, Jean‐Claude; Jaques Miret, Josep Anton; MacLeod, Alan; Navajas Navarro, Maria; Niere, Björn; et al.
Abstract: The EFSA Panel on Plant Health performed a pest categorisation of Palm lethal yellowing phytoplasmas for the EU territory. This name is used to describe diseases that share the same succession of symptoms in palms that are caused by a number of strains of phytoplasma, for which efficient molecular detection assays are available. The pest is not known to occur in the EU and therefore does not meet one of the criteria for being a Union regulated non‐quarantine pest. For ' Candidatus Phytoplasma palmae', the planthopper Haplaxius crudus, which is not known to be present in the EU, is the confirmed vector, but for the other strains, the vectors are unknown. The host range of the pest is restricted to Arecaceae species, in particular coconut. The pest is regulated on all known hosts in Annex IIAI of Directive 2000/29/EC. It could potentially enter the EU via plants for planting or through infected vectors. The phytoplasmas could become established in the EU as host plants are present. It is unknown whether arthropods present in the EU could be vectors. The potential impact of the pest if introduced into the EU is difficult to assess given this uncertainty but is estimated to be limited. The main knowledge gaps concern the status of potential vector insects in the EU; the possibility for seed transmission of the phytoplasmas; the origin and volume of the trade in palm seeds and plants for planting; the host status and susceptibility of many palm species grown in the EU and the potential new assignments of phytoplasmas to this categorisation that might have associated alternate hosts. Palm lethal yellowing phytoplasmas meet the criteria assessed by EFSA for consideration as Union quarantine pest.